Outbreak investigation of foot-and-mouth disease in cattle in Tigray region, Northern Ethiopia - Tesfaye, Adehanom Baraki; Assefa, Guash Abay; Shishaye, Leul Berhe; Abera, Bisrat Mesfin; Gebreanenya, Nechey Tsehaye; Gebregiorgis, Gebru Legesse; Dürr, Salome (Frontiers in Veterinary Science, 2023)
An investigation of a foot-and-mouth disease (FMD) outbreak was conducted between late October and mid-December 2019 in Tigray region. The outbreak investigation team collected epidemiological data from the six villages of Kafta Humera and Seharti Samre districts, including morbidity proportions, mortality proportions, and clinical signs, and cattle management and vaccination history were collected via participatory methods, including interviews and group discussions with local experts and farmers in Kafta Humera and reports from the district veterinarians in Seharti Samre. Twenty-two tissue samples were collected for laboratory confirmation. Overall, 4,299/9,811 (43.8%) and 13,654/16,921 (80.6%) cattle showed clinical signs for FMD in Kafta Humera and Seharti Samre, respectively. In Kafta Humera, the highest morbidity proportion was found in adult cows and heifers (48.1%), followed by 27.8% in oxen and 15.9% in calves. In Seharti Samre, the morbidity proportion was similar in all age groups at 81%. No death of FMD-suspected cattle was reported throughout the outbreak. The serotype of foot-and-mouth disease virus (FMDV) identified by laboratory analysis differed between the two districts (serotype O in Kafta Humera and serotype A in Seharti Samre). We, therefore, suggest that the outbreaks in the two districts occurred independently from each other. Experts and farmers were interviewed and believed that the outbreak in Kafta Humera was most likely caused by interaction between cattle and wildlife from the surrounding Kafta Sheraro National Park, which share common grazing land. This outbreak investigation showed that FMD can cause devastating cattle morbidity. A regular vaccination program against the identified circulating FMDV serotypes with sufficient coverage is required to avoid future outbreaks.